Spatial Approach for Modeling Tropospheric Ozone and Its Interaction with the Infrared Wave and Temperature in Bogotá, Colombia - Castro Diaz, Ivan Ricardo (2015)
The human activities increase the global emissions, especially those resulting from industrial activities in urban areas. The tropospheric ozone, which is a pollutant derived from the interaction of the chemical smog under the solar radiation impact, is being analyzed because of its palliative effect to the greenhouse phenomenon.The situation becomes strongly dangerous due to the consequences to the public sanitation and the radiative forcing increasing the superficial temperature under the cities’ smog. This layer retains the infrared and thermal waves causing a heat island effect.This research led a mixed methodology to combine the ETM+ sensor and the climate ground stations for describing the interaction between the urban pollution layer and the heat island phenomenon. A per-day ‘local’ dimming model was developed under four assumptions in order to understand the dynamics of the tropospheric ozone and the high temperatures.